Sustainable production of jojobyl alcohols and cell viability study. (5th October 2021) - Acherki, Hassan; Hurtado, Olivia; Bouaid, Abderrahim
Abstract: An innovative biorefinery approach has been applied to evaluate jojoba oil (JO) in high value‐added products. It consists of enzymatic transesterification using short (1‐propanol, 1‐butanol), medium linear (1‐octanol), and branched (2‐ethylhexanol) chain alcohols. The proposed biorefinery approach uses an integrated process for the production of jojobyl alcohol (JA) mixtures (11‐eicosenol, 13‐docosenol and 15‐tetracosenol) as products that can be used in pharmaceutical applications. The remaining fraction of fatty acid alkyl esters (FAAE) has a wide range of industrial uses and could be used as a promising alternative to conventional fuels, as it complies with EN14214, the European Biodiesel Norm. The separation of JA from FAAE was carried out by crystallization using a binary mixture of hexane and diethyl ether. After the separation step, the main properties of FAAE were determined. The results showed that the cold flow properties and oxidation stability of the FAAE fraction, obtained as co‐product during the process, have been improved with respect to transesterified JO. The use of 2‐ethylhexanol as an alcohol in the transesterification reaction increases the amount of the most valuable fraction containing JAs. In vitro cell viability was measured in HEK293T cells using the tetrazolium dye reduction (MTT) assay. The results showed that this oily liquid mixture of JA components ( cis ‐11‐eicosenol, cis ‐13‐docosenol, and cis ‐15‐tetracosenol) had a cytotoxic effect at concentrations of 10 and 100 μmol L −1 and no cytotoxic activity at 1 μmol L −1 . The concentration of 1 μmol L −1 does not, therefore, modify the cell viability, does not produce toxic effects in the tested cells and could be used as a therapeutic compound. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd